Competitiveness of entrepreneurs and salaried workers - Loukas Balafoutas; Mongoljin Batsaikhan; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2021)
We measure the willingness to compete of entrepreneurs and salaried workers in an experiment. We let participants choose between a piece-rate and a tournament scheme either in private or in public. We find that in the private condition entrepreneurs are less competitive than salaried workers, but that in the public condition this ordering is reversed. Data from a follow-up survey suggest that social image concerns of entrepreneurs and perceived norms can explain why entrepreneurs are more competitive when decisions are publicly observable. Our survey also reveals that more competitive entrepreneurs earn higher profits in their businesses.
hdl:21.11116/0000-0008-1913-7
Keywords: C91; C93; D01; L26; 330; Competitiveness; Entrepreneurs; Salaried Workers; Profits; Field Behavior; Experiment